2021
DOI: 10.3390/jof7020073
|View full text |Cite
|
Sign up to set email alerts
|

Species Diversity, Mating Strategy and Pathogenicity of Calonectria Species from Diseased Leaves and Soils in the Eucalyptus Plantation in Southern China

Abstract: Many Calonectria species are causal agents of diseases on several forestry, agricultural and horticultural crops. Calonectria leaf blight is one of the most important diseases associated with Eucalyptus plantations and nurseries in Asia and South America. Recently, symptoms of leaf rot and leaf blight caused by Calonectria species were observed in a one-year-old Eucalyptus experimental plantation in GuangXi Province, southern China. To better understand the species diversity, mating strategy and pathogenicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(100 citation statements)
references
References 53 publications
5
71
0
Order By: Relevance
“…Many species of Calonectria are important pathogens of agricultural, horticultural, and forestry crops and these species occur in approximately 335 plant species in nearly 100 plant families [1]. Species of Calonectria have been isolated from soils, fruits, leaves, stems, and roots [1,4,[7][8][9][10][11][12][13][14]. The fungi are best known as foliar, shoot, and root pathogens [1,2,4,5], and they are commonly associated with disease symptoms, including seedling damping-off, seedling rot, cutting rot, leaf spots, leaf blight, shoot blight, crown cankers, stem lesions, collar and root rots, and tuber rot [1,[14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many species of Calonectria are important pathogens of agricultural, horticultural, and forestry crops and these species occur in approximately 335 plant species in nearly 100 plant families [1]. Species of Calonectria have been isolated from soils, fruits, leaves, stems, and roots [1,4,[7][8][9][10][11][12][13][14]. The fungi are best known as foliar, shoot, and root pathogens [1,2,4,5], and they are commonly associated with disease symptoms, including seedling damping-off, seedling rot, cutting rot, leaf spots, leaf blight, shoot blight, crown cankers, stem lesions, collar and root rots, and tuber rot [1,[14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Calonectria ilicicola is a soil-borne fungal pathogen of worldwide importance that causes black rot disease in peanut and red crown rot in soybean [21,[24][25][26][27][28]. Recently, we isolated five Calonectria species, namely C. aconidialis, C. auriculiformis, C. hongkongensis, C. pseudoreteaudii, and C. reteaudii, from soils in a plantation of Eucalyptus trees [14]. Inoculation results showed that all five species caused leaf spot, leaf blight, and seedling rot to the tested Eucalyptus genotypes within three days [14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations